Evaluasi Pelaksanaan Pembelajaran Guru Matematika di SMK Negeri 2 Sinjai - Mutmainna, St. Nurul; Rahmah, Nuraziza; Danial; Syarifuddin; Fitriani (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Muhammadiyah Sinjai, 2023)
This study aims to study the implementation of mathematics teacher learning at SMK Negeri 2 Sinjai. This study used a qualitative research approach with a case study type of research. The results of the study show that the implementation of teacher learning at SMK Negeri 2 Sinjai includes teachers who pay attention to their students and are included in the category of good quality teachers, because the teacher first prepares matters relating to the learning process starting from the beginning of learning, the core of learning and cover the needs of students. Regarding the learning reflection process, the learning process from the beginning to the end of learning is good. Teachers and students together conclude the learning material studied, make improvements or solutions when finding errors in the teaching and learning process. As for the results of the analysis of the learning process with learning theory that the teacher uses learning theory which not only emphasizes the knowledge of students but the teacher also emphasizes the affective and psychomotor of students.